2021
DOI: 10.1259/bjro.20210009
|View full text |Cite
|
Sign up to set email alerts
|

Non-coplanar VMAT plans for postoperative primary brain tumour to reduce dose to hippocampus, temporal lobe and cochlea: a planning study

Abstract: Objectives: This study aimed to compare radiotherapy plan quality of coplanar VMAT (CO-VMAT) and non-coplanar VMAT (NC-VMAT) for postoperative primary brain tumour. Methods: A total of 16 patients who were treated for primary brain tumours were retrospectively selected for this study. For each patient, identical CT sets with structures were used for both CO-VMAT and NC-VMAT planning. For CO-VMAT, one full arc and two coplanar half arcs were used. For NC-VMAT, one full coplanar and two non-coplanar half arcs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We compared several dosimetric and technical parameters between non-coplanar and coplanar VMAT plans to evaluate the plan quality. The PTV coverage was similar with both the plans as well as the sparing of OARs as stated by the previous studies [ 13 , 17 ]. The D 1cc of the spine was much lesser with the non-coplanar plans.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We compared several dosimetric and technical parameters between non-coplanar and coplanar VMAT plans to evaluate the plan quality. The PTV coverage was similar with both the plans as well as the sparing of OARs as stated by the previous studies [ 13 , 17 ]. The D 1cc of the spine was much lesser with the non-coplanar plans.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, the coplanar full arc SBRT VMAT planning involves a simple beam arrangement but increases the irradiated volume. Some studies have compared NC-VMAT with C-VMAT for various sites like the lung, Brain, and Nasopharynx which showed the benefit of NC-VMAT plans over C-VMAT plans [16][17][18]. However, to the best of our knowledge, the application of manually selected beam orientation in VMAT plans generated with a limited number of ipsilateral partial arcs to avoid the possibility of gantry collision with the couch for liver SBRT has not been well studied.…”
Section: Comparison Between Volumetric Modulated Arc Therapy Based Co...mentioning
confidence: 99%
“…It has been applied for treating prostate cancer [6,7] and liver cancer [8,9] in coplanar VMAT and lung cancer in non-coplanar VMAT [10]. In view of cranial regions, previous studies suggested that non-coplanar VMAT demonstrated a dose reduction to organs at risk (OARs) located in the peripheral regions, including the hippocampus [11][12][13], normal brain tissue, the temporal lobe and the cochlea [14,15]. A significant dose reduction to these organs helped to minimize the side effects, such as cognitive decline and auditory impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that modification of co-planar VMAT plans may reduce dose to OARs [11][12][13][14][15][16]. For example, non-coplanar VMAT plans reduced the low dose to the heart during dose delivery, while an ipsilateral lung might expose to higher radiation dose [11].…”
Section: Introductionmentioning
confidence: 99%